A taxonomical review of the Gnathophausia (Crustacea, Lophogastrida), with new records from the northern mid-Atlantic ridge - Meland, K.; Aas, P. ?. (Zootaxa, 2013)
Taxonomy of 11 species contained within the Lophogastrida genus Gnathophausia is presented. We report new records of G. affinis, G. gigas, G. ingens, and G. zoea from the Atlantic Ocean between Iceland and the Azores. We also describe a new species, G. bergstadi that resembles G. zoea, but differs in having a heart-shaped apex on the telson and having the lower later keels of the carapace not fusing with the upper lateral keels. Gnathophausia is found to be most abundant at bathyal depths. G. zoea, G. gigas, and G. ingens are reported distributed throughout the world’s oceans. G. affinis and G. bergstadi are confined to Atlantic water masses, whereas G. childressi, G. longispina, and G. elegans, are found in the Pacific. A more limited distribution in tropical regions of the world’s oceans is observed in G. gracilis, and also G. fagei and G. scapularis that are confined to the South China Sea and Indian Ocean, respectively. We include an identification key and known distribution of all accepted Gnathophausia species.